Hubungan Tingkat Pengetahuan dan Sikap Mahasiswa Universitas Jambi terhadap Penerimaan Vaksinasi Covid-19 - Talitha Argani Thaharah; Ima Maria; Tia Wida Ekaputri (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
ABSTRACT Background: Interventions were carried out by the government. However, other interventions are needed with the Covid-19 vaccination. It’s expected that the chain of transmission can be broken. The risk of transmission of Covid-19 increases in certain sub-populations, including college students. College students are more educated and have a quick response to health problems. Thus it’s hoped that the knowledge and attitudes of students will be at a good level toward the acceptance of the Covid-19 vaccination. Methods: This research was an analytic observational study using a cross-sectional design which was conducted in September on 200 Jambi University students from seven faculties. Distribution of questionnaires via Google form. The data obtained were analyzed by Chi-square test. Results: From 200 respondents, most of the respondents had a low level of knowledge (51.5%) and a poor level of attitude (55%). The respondent's acceptance rate of the Covid-19 vaccination was 99.5%. Conclusion: Statistically, there’s no significant relationship between acceptance of Covid-19 vaccination and the level of knowledge of Jambi University students. In addition, there is no significant relationship between acceptance of Covid-19 vaccination program and the attitude level of Jambi University students. Keywords: Knowledge, Attitude, Acceptance, Covid-19 vaccination ABSTRAK Latar Belakang: Berbagai intervensi dilakukan pemerintah untuk menanggulangi Covid-19. Namun, diperlukan upaya intervensi lain dengan program vaksinasi Covid-19. Diharapkan rantai penularan dapat diputus, angka kesakitan dan kematian menurun, serta terbentuk herd immunity. Risiko penularan Covid-19 meningkat pada sub populasi tertentu, termasuk mahasiswa dengan kegiatan pembelajaran yang melibatkan banyak orang. Dibandingkan dengan sub populasi lainnya, mahasiswa lebih teredukasi, terbuka, dan memiliki respon sehingga diharapkan pengetahuan dan sikap mahasiswa pada tingkat yang baik terhadap penerimaan vaksinasi Covid-19. Metode: Rancangan penelitian yang digunakan adalah rancangan cross sectional yang dilakukan bulan September pada 200 mahasiswa Universitas Jambi dari tujuh fakultas. Kuesioner disebarkan secara daring pada responden. Data dianalisis dengan Uji Chi square. Teknik pengambilan sampel yang digunakan adalah metode multistage sampling. Hasil: Dari 200 responden, diketahui tingkat pengetahuan sebagian besar responden rendah (51,5%) dan tingkat sikap kurang baik (55%). Tingkat penerimaan vaksinasi Covid-19 responden sebesar 99,5%. Kesimpulan: Secara statistik tidak terdapat hubungan bermakna antara penerimaan vaksinasi Covid-19 dengan tingkat pengetahuan mahasiswa Universitas Jambi. Selain itu, tidak terdapat hubungan bermakna antara penerimaan vaksinasi Covid-19 dengan tingkat sikap mahasiswa Universitas Jambi. Kata kunci: Pengetahuan, Sikap, Penerimaan, Vaksinasi Covid-19